Microplastic occurrence and effects in commercially harvested North American finfish and shellfish: Current knowledge and future directions. Issue 1 (5th November 2019) - Baechler, Britta R.; Stienbarger, Cheyenne D.; Horn, Dorothy A.; Joseph, Jincy; Taylor, Alison R.; Granek, Elise F.; Brander, Susanne M.
Abstract: Commercial fisheries yield essential foods, sustain cultural practices, and provide widespread employment around the globe. Commercially harvested species face a myriad of anthropogenic threats including degraded habitats, changing climate, overharvest, and pollution. Microplastics are pollutants of increasing concern, which are pervasive in the environment and can harbor or adsorb pollutants from surrounding waters. Aquatic organisms, including commercial species, encounter and ingest microplastics, but there is a paucity of data about those caught and cultured in North America. Additional research is needed to determine prevalence, physiological effects, and population‐level implications of microplastics in commercial species from Canada, the United States, and Mexico. Investigations into possible human health effects of microplastic exposure from seafood are also greatly needed. This synthesis summarizes current knowledge, identifies data gaps, and provides future research directions for addressing microplastics effects in commercially valuable North American fishery species.